Hubungan Tingkat Pengetahuan Ibu Menyusui Tentang MP ASI Dengan Pemberian MP ASI Pada Bayi 0-6 Bulan di Puskesmas Kebun Handil Jambi - Rosdawati Rosdawati; Dormina Dormina (STIKES Garuda Putih, 2024)
Background: This study aims to determine the relationship between the level of knowledge of breastfeeding mothers about MP ASI and the provision of MP ASI to babies 0-6 months at the Kebun Handil Community Health Center which was carried out from May-June 2023.Method: Descriptive analytical research type with a cross-sectional approach. The population and sample are mothers who have toddlers aged 6-24 months in the working area of the Kebun Handil Community Health Center, taken using accidental sampling technique. The research instrument used a questionnaire, data was analyzed univariately and bivariately with the Spearman Rank (Rho) percentage test.Results: Characteristics of mothers under five in the Kebun Handil Community Health Center working area in 2023, most of them are 20-35 years old (78.4%), have secondary education (47.1%), are housewives (66.7%), and the majority have children. between 1-2 years (52.9%). The knowledge of mothers about MP-ASI for toddlers aged 6-24 months is mostly high, namely 54.9% or 28 mothers and the behavior of giving MP-ASI to toddlers. Most of the mothers who visit the Kebun Handil Health Center mostly behave well, amounting to 49. 0% or 25 people provide MP-ASI. The results of the Spearman rank test show that the X2-calculation value is 0.480 and p-value = 0.000. Conclusion: There is a relationship between the level of maternal knowledge about MP-ASI and the behavior of giving MP-ASI to toddlers aged 6-24 months at the Kebun Handil Health Center, Jambi in 2023 Keywords: Level of Knowledge, MP-ASI, Behavior, Community Health Center